2019
DOI: 10.1021/acs.jpcc.9b05062
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transitions of Charge Density Wave Order in Epitaxial Few-Layered 1T′-VTe2 Films

Abstract: Charge density wave phase comprises a periodic modulation of the electronic charge density with a periodic distortion of the atomic lattice, and transition-metal dichalcogenides are very important subjects for the study of this distortion. In this work, large-area 1T′-vanadium telluride (VTe2) films grown by molecular beam epitaxy show the charge density wave order down to the few-layer limit. The film thickness was found to be strongly correlated with the out-of-plane vibration mode shifting from Raman scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…Both types 1 and 2 CDW phases possess a lattice structure of ( C 2/ m ) and the same transition temperature to the common symmetric 1T phase ( P ‐3 m 1) of T = 480 K. We have extended the temperature range of the Laue diffraction measurement down to a temperature of 30 K, and no other phase transition has been observed (Figure S5, Supporting Information). Moreover, temperature‐dependent X‐ray absorption spectroscopy confirms the absence of other phase transition (Figure S6, Supporting Information); this result contrasts with the multiple CDW transitions in a film of VTe 2 on graphene, grown by molecular beam epitaxy 18,21. We note that polymorphic CDW phases, in VTe 2 as well as in other materials, have been identified for the first time in this study, which highlights the original platform (VTe 2 ) for investigating polymorphic quantum states including spin, charge, and lattice waves.…”
Section: Electrical Properties Of the Types 1 And 2 Cdw Phases In Vtesupporting
confidence: 55%
See 2 more Smart Citations
“…Both types 1 and 2 CDW phases possess a lattice structure of ( C 2/ m ) and the same transition temperature to the common symmetric 1T phase ( P ‐3 m 1) of T = 480 K. We have extended the temperature range of the Laue diffraction measurement down to a temperature of 30 K, and no other phase transition has been observed (Figure S5, Supporting Information). Moreover, temperature‐dependent X‐ray absorption spectroscopy confirms the absence of other phase transition (Figure S6, Supporting Information); this result contrasts with the multiple CDW transitions in a film of VTe 2 on graphene, grown by molecular beam epitaxy 18,21. We note that polymorphic CDW phases, in VTe 2 as well as in other materials, have been identified for the first time in this study, which highlights the original platform (VTe 2 ) for investigating polymorphic quantum states including spin, charge, and lattice waves.…”
Section: Electrical Properties Of the Types 1 And 2 Cdw Phases In Vtesupporting
confidence: 55%
“…The bond length difference between types 1 and 2 is limited to 0.1 Å, but the Laue diffraction patterns precisely reveal that the unit cell of the type 2 CDW is three times larger than that of type 1. Overall, the new phase, type 2 CDW, has an additional lattice distortion along the b ‐axis that has not been observed in previous reports on CDWs in VTe 2 ;15–19,21 the intervanadium distance of 3.61 Å along the b ‐axis is split into 3.52 and 3.65 Å, as shown in the right panel of Figure 2a.…”
Section: Electrical Properties Of the Types 1 And 2 Cdw Phases In Vtesupporting
confidence: 48%
See 1 more Smart Citation
“…These peculiarities enable it to specialize in designing various heterojunction structures and fabricating those thermolabile TMDs. Accompanied by the successful applications in preparing 2H phase group VIB TMDs [144][145][146][147] and metallic VTe 2 , [148][149][150] many attempts for their metallic phase counterparts have been carried out, and several critical growth conditions in MBE process are revealed detailedly. What's more, MBE method is particularly suitable for the preparation of TMDs with nanoisland morphology.…”
Section: Molecular Beam Epitaxy Methodsmentioning
confidence: 99%
“…On the other hand, monolayer VTe 2 stabilizes with the 1T structure [28][29][30][31][32][33] and exhibits the 4×4 CDW [25][26][27] . Although the relationship between fermiology and PLD as well as the origin of different crystal structures between monolayer and bulk have been intensively discussed, these key questions 34,35 are still controversial [34][35][36][37] . Previous studies also reported that multilayer VTe 2 exhibits the 2×1 periodicity distinct from bulk and monolayer 34,35,37 , but the consensus on the origin of the 2×1 periodicity and its link to possible CDW properties has not yet been obtained.…”
Section: Introducitonmentioning
confidence: 99%